MOTIVATIONS, ATTITUDES AND READING PRACTICES OF STUDENTS MEXICANS AND THE LEVEL OF PERFORMANCE IN READING THE PROOF OF PISA 2009. - David Castro Porcayo (Tendencias Pedagógicas, 2015)
The purpose of this article is to outline patterns of behavior, attitudes and motivations of Mexican students and their relationship with the level of performance achieved in reading literacy (PISA 2009). The study was conducted based on the information provided the construct "Reading for pleasure" contained in the instrument: Student Questionnaire. The approach was conducted from two perspectives: as a semiotic object, based on the analysis of the term "pleasure" from their theoretical and conceptual screening system, and as a hypothetical entity, for which the construct was analyzed in terms of categories, variables and indicators in it. Finally, the results were